A Novel High Throughput Invasion Screen Identifies Host Actin Regulators Required for Efficient Cell Entry by Toxoplasma gondii - Gaji, Rajshekhar Y. (Public Library of Science, 2013)

(untitled)
Toxoplasma gondii critically relies on cell invasion as a survival strategy to evade immune clearance during infection. Although it was widely thought that Toxoplasma entry is parasite directed and that the host cell is largely a passive victim, recent studies have suggested that host components such as microfilaments and microtubules indeed contribute to entry. Hence to identify additional host factors, we performed a high-throughput siRNA screen of a human siRNA library targeting druggable proteins using a novel inducible luciferase based invasion assay. The top 100 hits from the primary screen that showed the strongest decreases in invasion were subjected to confirmation by secondary screening, revealing 24 proteins that are potentially involved in Toxoplasma entry into host cells. Interestingly, 6 of the hits appear to affect parasite invasion by modifying host cell actin dynamics, resulting in increased deposition of F-actin at the periphery of the cell. These findings support the emerging notion that host actin dynamics are important for Toxoplasma invasion along with identifying several novel host factors that potentially participate in parasite entry.